Examining the Practice of Teacher Leadership Across Nevada: How Is Context Associated with Practice? - Wiens, Peter D.; Hinton, KaaVonia; Pritchard, Ami (International Journal of Education Policy and Leadership, 2025)
Teacher leadership (TL) is recognized as vital to creating effective schools with demonstrated benefits to principals, teachers, and students. Teacher leadership is defined in this study as teachers leading from within and beyond the classroom in both formal and informal capacities. TL can take the form of a variety of behaviours such as professional learning, the leading of professional development, collaboration, shared leadership, and equity leadership. While there are commonalities, the practical applications of TL can vary greatly from context to context. Even within specific policy contexts, TL can vary from school to school. This article analyzed the responses of 1,274 public school teachers in Nevada using the Survey of Teacher Leadership and shows patterns in the frequency of TL practices across contexts.